PENGENDALIAN EMISI KARBON DAN PERUBAHAN STRUKTUR NAFKAH RUMAH TANGGA PETANI: ANALISIS SOSIOLOGI NAFKAH - Hadi Dharmawan, Arya; Budi Prasetyo, Lilik; Tonny Nasdian, Fredian (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTThe development of carbon-based society is one of the contemporary issues that offers a form of environmental and human collaboration respirokal also functional in controlling the risks of climate change.However, its not easy to introduce the issue of carbon to the livelihood systems of rural communities. In it, found a variety of problems, from technical aspects to non-technical. This study was constructed to answer these issues in the wider framework to mitigate climate change by carbon credits in two different locations, namely in the Daerah Istimewa Yogyakarta (DIY) and Jambi. For the case of DIY, carbon trading scheme, which is based on the Voluntary Carbon Market (VCM) still pose a constraint on the aspect of “legalization” and “market”. Besides the licensing process and the disharmony between institutions vertically led to increasingly complex problems. As for the case in Jambi Province, the forest is seriously threatened by forest fires and property issues (tragedy of the common), the lack of public knowledge about the functioning of Forest Park (TAHURA) causes some people consider the forest and the free open access to be entered.In another side, the TAHURA is one potential area that has a large enough carbon stocks as the area of climate change mitigation. This research is ultimately going to map out the problems and calculate the economic contribution obtained by the public, as well as changes in the structure of living in two locations with two carbon initiatives of community-based schemes are different.Keywords: mitigation of climate change, carbon emissions, the development of community-based carbon, a living structure, sociology of rural livingABSTRAKPengembangan karbon berbasis masyarakat merupakan salah satu isu kontemporeryang menawarkan bentuk kolaborasi manusia dan lingkungan yang respirokal juga fungsional dalam upaya pengendalian resiko perubahan iklim.Namun, tidak mudah memperkenalkan isu karbon ke dalam sistem penghidupan masyarakat pedesaan. Di dalamnya,ditemukanberbagai permasalahan, dari aspek teknis hingga non-teknis. Penelitian ini dikonstruksikan untuk menjawabberbagai persoalan tersebut dalam kerangka besar mitigasi perubahan iklim via kredit karbon di dua lokasi yang berbeda, yakni di Provinsi Daerah Istimewa Yogyakarta (DIY) dan Provinsi Jambi. Untuk kasus di DIY, skema perdagangan karbon yang berlandaskan pada Voluntary Carbon Market (VCM) masih menimbulkan kendala pada aspek “legalisasi” dan “pasar”. Selain itu proses perizinan dan disharmoni antar lembaga secara vertikal menyebabkan persoalan semakin kompleks. Sedangkan untuk kasus di Provinsi Jambi, hutan pada saat ini sangat terancam dengan kebakaran hutansertapersoalan properti (tragedy of the common), minimnya pengetahuan masyarakat tentang fungsi Taman Hutan Raya (TAHURA) menyebabkan sebagian masyarakat menganggap kawasan hutan tersebut open access dan bebas untuk dimasuki.Di sisi lain, kawasan TAHURA merupakan salah satu kawasan potensial yang memiliki cadangan karbon yang cukup besar sebagai kawasan mitigasi perubahan iklim. Penelitian ini pada akhirnya hendak memetakan permasalahan dan mengkalkulasikan kontribusi ekonomi yang diperoleh oleh masyarakat, serta perubahan struktur nafkah di dua lokasi dengan dua skema inisiatif karbon berbasis masyarakat yang berbeda.Kata kunci: mitigasi perubahan iklim, emisi karbon, pengembangan karbon berbasis masyarakat, struktur nafkah, sosiologi nafkah pedesaa